2010
DOI: 10.1016/j.brainres.2010.01.084
|View full text |Cite
|
Sign up to set email alerts
|

Stress rapidly increases alpha 1d adrenergic receptor mRNA in the rat dentate gyrus

Abstract: The hippocampal formation is a highly plastic brain region that is sensitive to stress. It receives extensive noradrenergic projections, and noradrenaline is released in the hippocampus in response to stressor exposure. The hippocampus expresses particularly high levels of the α 1D adrenergic receptor (ADR) and we have previously demonstrated that α 1d ADR mRNA expression in the rat hippocampus is modulated by corticosterone. One of the defining features of a stress response is activation of the hypothalamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Therefore, rapid changes to striatum adenosine receptor mRNA observed immediately following tail shock may not be representative of later time points. Other G-protein coupled receptors that display altered mRNA levels immediately following uncontrollable tail shock return to baseline levels within hours [119], or can continue to change expression days later [73]. It is possible that A 1 R or A 2A R mRNAs may also display differing patterns of expression overtime.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rapid changes to striatum adenosine receptor mRNA observed immediately following tail shock may not be representative of later time points. Other G-protein coupled receptors that display altered mRNA levels immediately following uncontrollable tail shock return to baseline levels within hours [119], or can continue to change expression days later [73]. It is possible that A 1 R or A 2A R mRNAs may also display differing patterns of expression overtime.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been documented that stress affects the expression of receptors for these stress hormones (20,60). In addition, stress and glucocorticoids rapidly increase ␣ 1 d-ADRs in vivo in rat dentate gyrus (7), and in vitro experiments have shown that glucocorticoids can upregulate ␣ 1 d-ADR mRNA expression (58).…”
mentioning
confidence: 99%
“…Although Leydig cell steroidogenesis is mainly activated through LH/hCG receptors, regulation itself is a multicompartmental process comprised of neural (61) and complex endocrine, paracrine, and autocrine signaling pathways (22, 51, 59) including cGMP (4) and adrenergic signaling (3). All the aforementioned elements of steroidogenic machinery might be involved in the regulation of testicular steroidogenesis, providing an adaptive mechanism by which testicular structures, including Leydig cells, recover from disturbed homeostasis, such as stress, or any other situation disturbing testosterone homeostasis.It is well established that the organism responds to stress, a state of perceived threat to homeostasis, by activating the sympathetic nervous system, secreting catecholamines and glucocorticoids in the "fight-or-flight" response (7,8,20,24,39,55,60). The ability of stress to inhibit reproductive functions is well documented (21,23,24,36,37,49,55), and the mechanisms mediating these effects depend on the type, duration, and frequency of the stimulus (24,39,55) as well as on the influence of the steroid milieu on adrenergic and opiate components that have an impact on the hypothalamo-pituitarygonadal axis (21,23,24,36,37,49,55).…”
mentioning
confidence: 99%
“…Given that, BDNF is required for consolidation of hippocampal-dependent memory (Alonso et al 2002a, b;Tyler et al 2002), a reduction in this plasticityrelated molecule could be critical for the hippocampal-dependent memory disturbances produced by US. And finally, although the mechanisms for stressorand pathogen-evoked cytokine release are not interchangeable (Campeau et al 2010;Campisi et al 2012;Maslanik et al 2012), it is interesting to note that wheel running was recently reported to reduce hippocampal microglia activation, brain proinflammatory cytokine responses, and BDNF reductions after peripheral bacterial challenge in older rats (Barrientos et al 2011) lending additional support to our hypothesis that regular physical activity may quiet stressor-evoked hippocampal microglia activation, and protect against BDNF down-regulation and reduced neurogenesis.…”
Section: Mechanisms For Stress Robustness Produced By Physicalmentioning
confidence: 78%